Regulation of Sap Release when Tapping Betula pendula Roth - Anatoly V. Gryazkin; Dmitriy A. Danilov; Dmitriy A. Zaytsev; Minh Anh Hoang; Tran Trung Thanh (Лесной журнал, 2023)
The study showed a correlation between the intensity of sap release by birch trees and the trunk diameter, degree of crown development, and tree age. In addition to the characteristics of trees, sap release intensity also depended on weather conditions and tapping methods. The study object was a mature birch stand with blueberry ground cover (Kirishi forestry unit of the Leningrad region, Russia). The composition of the stand consisted of birch (65 %), spruce (21 %), aspen (8 %), alder (3 %), elm (2 %), and maple (1 %); the basal area was 0.6. The projective cover was 0.73. The average age, diameter and height were 76 yrs, 25.0 cm and 24.3 m, respectively. Tapping was carried out by the closed method. The tapping channels were 30–40 cm above the root neck. The intensity of sap release was found to depend on the number of channels and their location. The maximum intensity of sap release from one tapping channel was 285 mL/h, depending on the trunk diameter and tree age. The intensity of sap release varied throughout the day: it increased in the morning and early afternoon (until 1–2 pm), and decreased in the late afternoon. At night, sap release intensity was the lowest, or it stopped completely regardless of the tree's age, degree of crown development, and trunk diameter. At the average daily temperature between +3 and +6 °С in moky weather, each tree produced 0.54–1.37 L of sap per day, and at a higher temperature in sunny weather, 2.50–6.22 L per day. The higher the air and soil temperatures, the more intense the sap release. At the air temperature of –3.0 °С, the sap freezes. When the average daily air temperature stays above +10.0 °С for several days, the sap begins to ferment. For citation: Gryazkin A.V., Danilov D.A., Zaytsev D.A., Hoang Minh Anh, Thanh Tran Trung. Regulation of Sap Release when Tapping Betula pendula Roth. Lesnoy Zhurnal = Russian Forestry Journal, 2023, no. 4, pp. 180–189. (In Russ.). https://doi.org/10.37482/0536-1036-2023-4-180-189